Survei Kondisi Fisik Atlet Pusat Pelatihan Muaythai - Wicaksono, Ajeng Suko; Hariyanto, Eko (Sport Science and Health, 2021)
Abstract: This study aims to determine the level of physical condition of muaythai athletes at the training center of Malang Regency. Using a quantitative descriptive design. The instrument in this study used a physical condition skill test. The type of test used was a test of strength, muscle explosive power, speed, and vo2max endurance. The results of the research on the physical condition of Muaythai athletes in the training center of Malang Regency: (1) Abdominal Muscle Strength in the male category on average 50% less, while the female category is average 62% (2) Arm muscle strength in the male category is 57% less while the category female on average 100% less (3) Explosive Power of leg muscles in the male category on average 33% less while the female category is average 17% (4) the 30 sprint category for the male category is average 67% while the female category is average moderate 67% (5) The average vo2max endurance of the boys was 33% less, while the female category was 17% on average.Â Abstrak: Penelitian ini bertujuan untuk mengetahui tingkat kondisi fisik pada atlet muaythai pusat pelatihan Kabupaten Malang. Mengunakan rancangan deskriptif kuantitatif. Instrumen dalam penelitian ini mengunakan tes keterampilan kondisi fisik, Jenis tes yang digunakan tes kekuatan, daya ledak otot, kecepatan, dan daya tahan vo2max. Hasil penelitian kondisi fisik atlet Muaythai pusat pelatihan Kabupaten Malang: (1) Kekuatan Otot Perut kategori putra rata-rata 50% kurang sedangkan kategori putri rata-rata sedang 62% (2) Kekuatan Otot Lengan kategori putra rata-rata 57% kurang sedangkan kategori putri rata-rata kurang 100% (3) Daya Ledak Otot tungkai kategori putra rata-rata 33% kurang sedangkan kategori putri rata-rata sedang 17% (4) sprint 30 kategori putra rata-rata sedang 67% sedangkan kategori putri rata-rata sedang 67% (5) Daya tahan vo2max putra rata-rata 33% kurang sedangkan kategori putri rata-rata sedang 17%.